2022
DOI: 10.20961/lar.v20i3.63273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of date (Phoenix dactylifera L.) pit flour as alternative feed ingredients on egg quality of laying hens

Abstract: <p class="MDPI17abstract"><strong>Objective: </strong>The aims this study of evaluate the effect of use date (<em>Phoenix dactylifera</em> L.) pits as alternative feed ingredient on egg quality of laying hens.</p><p class="MDPI17abstract"><strong>Methods: </strong>This study was designed to consist of 5 treatments and 5 replications using a Completely Randomized Design (CRD) and if the effect was significant (P&gt;0.05) or very significant (P&gt;0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[5,12] reported that Lactobacillus acidophilus could increase protein digestibility, protein plays an important role in binding calcium in the form of calcium binding protein (CaBP), this complex is able to facilitate calcium absorption and store it to form egg shells and improve the quality of the shell structure. Besides the calcium absorption, [13] also explained that protein content correlates with egg weight and the protein as well as energy are required for the growth and production of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…[5,12] reported that Lactobacillus acidophilus could increase protein digestibility, protein plays an important role in binding calcium in the form of calcium binding protein (CaBP), this complex is able to facilitate calcium absorption and store it to form egg shells and improve the quality of the shell structure. Besides the calcium absorption, [13] also explained that protein content correlates with egg weight and the protein as well as energy are required for the growth and production of laying hens.…”
Section: Introductionmentioning
confidence: 99%